2019
DOI: 10.1051/sicotj/2019031
|View full text |Cite
|
Sign up to set email alerts
|

Historically, did Cemented Thompson perform better than uncemented Austin Moore hemiarthroplasty for femoral neck fractures? A meta-analysis of available evidence

Abstract: Introduction: Thompson and Austin Moore prostheses have been commonly used in hemiarthroplasties for displaced femoral neck fractures. There has been considerable debate about which of these prostheses is preferred. The purpose of this meta-analysis was to compare historical data for clinical outcomes of cemented Thompson and uncemented Austin Moore hemiarthroplasty in displaced femoral neck fractures. Methods: We searched Medline via PubMed, Cochrane Central, Scopus, Ovid and Web of Science for relevant artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…6,10 In a 2019 review based on 4 RCTs and 6 observational studies, lower pooled reoperation and revision rates for cemented HA were reported. 11 In our study, based on more RCTs, we showed no significant differences. New findings include no significant differences in vascular complications (e.g.…”
Section: Comparison With Previous Workmentioning
confidence: 41%
See 2 more Smart Citations
“…6,10 In a 2019 review based on 4 RCTs and 6 observational studies, lower pooled reoperation and revision rates for cemented HA were reported. 11 In our study, based on more RCTs, we showed no significant differences. New findings include no significant differences in vascular complications (e.g.…”
Section: Comparison With Previous Workmentioning
confidence: 41%
“…Unlike previous reviews, we have compared outcomes separately for contemporary and non-contemporary implants and reported new findings. The majority of previous reviews in this area evaluated mortality at oneyear or at undefined time points, 7,8,10,11 whereas our review evaluated multiple time points (peri-operative, 30day, 1 year). The finding of longer operative time associated with cemented HA is consistent with previous reviews, [6][7][8]10,12 as are no significant differences in complications such as infection and dislocation.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
See 1 more Smart Citation